Determinants of Paying Zakat Through E-Zakat in Tarakan - Ichsan, Nurul; Fuadiyah, Hilmatul (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The existence of adequate infrastructure, especially in the Tarakan City area, makes the author utilize the integration of the conceptual approaches of the Technology Acceptance Model and the Theory of Planned Research Objectives: This study aims to analyze the influence of variables from the Technology Acceptance Model (TAM) theory and the Theory of Planned Behavior (TPB) on the interest in paying zakat, infaq, and alms through e-zakat.Research Methods: This study uses primary data from the distribution of questionnaires using the purposive sampling method with 111 respondents who are Muslim and domiciled in Tarakan City. The research method is the Structural Equation Model (SEM) Partial Least Square (PLS) approach.Empirical Results: The results obtained that attitudes and behavioral control have a significant influence on the interest in use, while the perception of usefulness, perception of ease, and subjective norms do not have a significant influence on the interest in paying zakat, infaq, and alms through e -zakat.Implications: The community still feels comfortable and easy to pay ZIS directly and the presence of people close to them or the surrounding environment has not fully provided confidence to the Muslim community of Tarakan City to use e-zakat as a payment service.JEL Classification: H71, H76, Q53